Pemberdayaan Kemitraan Masyarakat bagi Pengembang Perumahan Masyarakat Berpenghasilan Rendah dalam Membangun Perumahan yang Murah, Nyaman dan Hemat Energi: (The Empowerment of Community Partnerships for Low-Income Community Housing Developers in Building Low Cost, Comfortable and Energy-Efficient Housing) - Kindangen, Jefrey I.; Mandey, Johansen; Tangkuman, Stenly; Marbangun, Laksamana; Liem, Cindy; Takaliuang, Adnan (Vivabio: Jurnal Pengabdian Multidisiplin, 2024)
The role of developers is crucial in addressing the housing requirements of low-income communities; they have made an effort to construct basic houses at a reasonable cost. The majority of low-cost houses in North Sulawesi are equipped with zinc or metal roofs, which frequently result in the residents experiencing excessive heating and discomfort. The Community Partnership Empowerment team has installed roof ventilation and incorporated radiative insulation technology in this activity, utilising recycled cardboard. These two technologies have the potential to substantially reduce the temperature of the attic and the room, as indicated by the research findings. The initial phase entails the identification of the needs of novice home builders, the dissemination of information regarding roof ventilation and radiative insulation technology, the provision of training to builders, the construction of houses that incorporate these technologies, the provision of marketing support to developers, and the conduct of evaluations only after production. The outcomes of each of these stages have been documented, including the misconception that the construction of a comfortable and energy-efficient low-cost house will necessitate a substantial outlay. Consequently, the team disseminated the information through technology applications that did not necessitate substantial expenditures during the dissemination phase. The contractors were instructed by the team on the installation of roof radiative insulation, the production of radiative insulation panels, and the installation of roof vents. The subsequent phase involves the construction of a high-quality, energy-efficient, and cost-effective residence. The primary consumers of low-cost houses are the majority of daily employees from government offices, the TNI, and the National Police, as well as a limited number of civil servants. Consequently, we are committed to improving our marketing initiatives by concentrating on the following: preserving the company's brand, guaranteeing the quality of the homes we sell, collaborating with the appropriate agencies of the Ministry of PUPR, and facilitating infrastructure in residential areas through government subsidies, banks, and other related elements. Once the marketed products have been constructed, we evaluate this program. The program's objective is to make a substantial contribution to the mitigation of climate change by reducing carbon emissions. It ensures the comfort and energy efficiency of residents in a cost-effective residence by prioritising their material and non-material well-being. ABSTRAK Dalam memenuhi kebutuhan perumahan terutama untuk masyarakat berpenghasilan rendah, peranpengembang sangat penting; telah berupaya untuk membangun rumah sederhana dengan harga yangterjangkau. Kebanyakan rumah sederhana di Sulawesi Utara dibangun dengan atap seng atau metal, inisering menjadi penyebab pemanasan yang berlebihan yang menimbulkan ketidaknyamanan penghunirumah. Dalam kegiatan ini tim Pemberdayaan Kemitraan Masyarakat telah memperkenalkan teknologiinsulasi radiatif yang terbuat dari kardus bekas dan pemasangan ventilasi atap. Berdasarkan hasilpenelitian, kedua teknologi ini dapat menurunkan suhu loteng dan suhu ruangan secara signifikan. Tahappertama dilakukan identifikasi kebutuhan para pengembang rumah sederhana, diseminasi pengetahuantentang teknologi insulasi radiatif dan ventilasi atap, pelatihan kepada para tukang, produksi rumahdengan aplikasi teknologi tersebut, pendampingan terhadap pemasaran kepada pengembang dan evaluasiyang baru akan dilakukan setelah produksi. Hasil dari setiap tahapan tersebut telah dicatat yakni:kesalahpahaman bahwa untuk membangun rumah sederhana yang nyaman dan hemat energi akanmembutuhkan biaya yang besar, untuk itu tim melakukan diseminasi berupa aplikasi teknologi dengantidak memerlukan biaya yang besar yang dilakukan pada tahap diseminasi. Para tukang diberi pelatihandalam memasang insulasi radiatif atap serta bagaimana memproduksi panel insulasi radiatif tersebut sertapemasangan ventilasi atap. Tahapan selanjutnya adalah produksi rumah dengan kualitas yang baik yangmurah, nyaman dan hemat energi. Jenis konsumen rumah sederhana paling banyak pegawai harian lepasdari kantor pemerintah, TNI dan Polri dan sebagian kecil PNS/ASN; sehingga dalam upayamengembangkan pemasaran dilakukan secara kontinyu terutama mempertahankan branding perusahaan,kualitas rumah yang dijual, kerjasama dengan pemerintah dengan instansi terkait KemenPUPR termasukpola subsidi pemerintah, infrastruktur kawasan permukiman yang difasilitasi pemerintah, pihak bank, danunsur lain terkait. Evaluasi terhadap program ini dilakukan setelah produk yang dipasarkan terbangun. Iniakan menjadi program yang memberikan kontribusi yang berarti terhadap pengurangan emisi karbonsebagai upaya mitigasi perubahan iklim; untuk kesejahteraan penghuni baik secara matrial maupun nonmaterial yang kenyamanan yang penghematan energi yang digunakan dalam rumah sederhana tersebut.